PERAN KOMUNITAS RELAWAN ANAK SUMATERA SELATAN DALAM MEMBENTUK KARAKTER PERCAYA DIRI ANAK JALANAN (STUDI KASUS DI KECAMATAN GANDUS KOTA PALEMBANG) - Muhammad Fadil Annafi; Abdullah Idi; Muhammad Fauzi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
This study discusses the Community that was founded in the city of Palembang, which cares about the lives of street children condition, especially in the city of Palembang. Street children who do not get an education either at school or at home. There are 117 children in the city ofPalembang unable to attend school. The data was obtained from the Palembang ministry of social services. Education is an important thing for street children to meet the future, with the education process can help children achieve what they dream ofThe research method used is a qualitative method with a case study approach and data collection techniques obtained through observation, interviews, and documentation obtained through primary data, namely administrators and volunteer who teach as resource person. For the analysis of the data themselves the authors use data reduction, data presentation and data verification.The results obtained through the field, interview with management of the South Sumatera Children Voulenteer the role of the community of South Sumatera children’s volunteers in forming the self confidance character education of street children in Palembang has Supporting and inhibiting factors, these supporting factors include: (1) Support from the goverment Palembang city in the from of financial aid and learning. (2) Teachers or educators. (3) Facilities for learning and teaching and learning equipment. The inhibiting factors include: (1) Students. and (2) Schedule.